ARE PATIENTS ON MAINTENANCE HEMODIALYSIS UNDER-WEIGHT? A COMPARATIVE ANALYSIS OF ACHIEVED BODY WEIGHT TO IDEAL BODY WEIGHT IN MAINTENANCE HEMODIALYSIS PATIENTS. - Arif, Atiya; Qayyum, Ahad (Pakistan Journal of Kidney Diseases, 2021)
Introduction: Various markers have been studied in End stage renal disease (ESRD) patients to evaluate the nutritional status of this population group with each one either involving a blood sample or tedious expensive monitor applications. Most notably serum albumin, serum cholesterol, C reactive protein and body composition monitor (BCM) have been studied. The aim of this study is to assess in ESRD patients to achieve their ideal body weight and assess the prevalence of malnutrition. Methods: We conducted a cross sectional study whereby all patients on thrice per week maintenance hemodialysis regimens at Bahria Town International Hospital Dialysis Unit had their ideal body weight calculated using standard formulae and then compared with the achieved body weight of the patient. The data analysis was done using SPSS software version 20.0. Results: A total of 60 patients (30 male and 30 female) who were on thrice/week maintenance hemodialysis at Bahria Town International Hospital Dialysis Unit were included in the study. Out of the 60 participants, 31 patients (51.7%) had an achieved dry body weight greater than ideal body weight while 21 patients (35%) had an achieved dry body weight less than ideal body weight and 8 patients (13.3%) had an achieved dry body weight equal to ideal body weight +/-2kg. Conclusion: The study shows that the majority of the ESRD patients on maintenance hemodialysis were achieving their target dry body weight in reference to ideal body weight. Further studies are needed to validate the role of ideal body weight in assessing malnutrition.